DARIER DISEASE –A RETROSPECTIVE SERIES OF 67 CASES - Nišević, Nađa; Nikolić, Aleksandra; Mihajlović, Milica; Elboursh, Dušan; Radanović, Dražen (HEALTH CARE, 2026)
Introduction/Aim: Darier disease is a rare autosomal dominant genodermatosis caused by mutations in the ATP2A2 gene and characterized by distinct clinical and histopathological findings. The aim of this study was to present the epidemiological and therapeutic characteristics of patients with Darier disease treated at a tertiary care center over a fifteen-year period.Methods: A retrospective cohort study including 67 patients diagnosed with Darier disease and treated at the Clinic of Dermatovenereology, University Clinical Center of Serbia, Belgrade, Republic of Serbia, was conducted. The diagnosis was established based on characteristic clinical presentation and histopathological confirmation. Epidemiological, clinical, and therapeutic characteristics were analyzed.Results: Female predominance (66%) was observed in the study population, while the first skin lesions most commonly appeared during adolescence and early adulthood. Positive family history was recorded in 48% of patients, supporting the autosomal dominant inheritance pattern. Lesions were predominantly localized on the trunk (85%). Neuropsychiatric comorbidities were observed in 16% of patients. Topical therapy was used in all patients, whereas systemic retinoids were administered in 51% of patients, predominantly in generalized forms of the disease. Conclusion: The results highlight the chronic course of the disease, marked phenotypic variability, and the need for individualized therapeutic approaches.
Keywords: Darier disease, genodermatosis, epidemiology, therapy